2020
DOI: 10.1002/bsd2.153
|View full text |Cite
|
Sign up to set email alerts
|

Green and grey: Nutritional lifestyle and healthful ageing in rural and urban areas of three sub‐Saharan African countries

Abstract: Increased lifespan has resulted in a growing ageing population with non‐communicable diseases (NCDs) like cardiovascular disease, diabetes, cancer, among others that are chronic in nature. Thus, causing dependency, disability, poor quality of life, and increased medical costs. This paper uses South Africa, Ghana, and Uganda to understand how improved medical interventions and social‐economic conditions have increased life expectancy while changing dietary and disease patterns. The countries are chosen due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…The population dynamics of the rapid and major demographic transitions associated with socio-economic development and accompanied by an epidemiological transition have emerged in industrialised countries and across sub-Saharan African (SSA) countries. The emergence of demographic and epidemiological transitions has led to a decrease in widely known acute infectious diseases and a rising prevalence of non-communicable diseases (NCDs) and chronic degenerative diseases ( 1 , 2 ). This increased burden of disease and the double burden of malnutrition (undernutrition and over-nutrition) in low-income countries have become a public health concern, which has received attention from both health and non-health experts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population dynamics of the rapid and major demographic transitions associated with socio-economic development and accompanied by an epidemiological transition have emerged in industrialised countries and across sub-Saharan African (SSA) countries. The emergence of demographic and epidemiological transitions has led to a decrease in widely known acute infectious diseases and a rising prevalence of non-communicable diseases (NCDs) and chronic degenerative diseases ( 1 , 2 ). This increased burden of disease and the double burden of malnutrition (undernutrition and over-nutrition) in low-income countries have become a public health concern, which has received attention from both health and non-health experts.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated a high prevalence of over-nutrition, which has increased by more than 33.0% ( 5 , 6 ), contributing to a rapid rise in the NCD burdens in Africa ( 2 , 7 ). The yearly contributions of each of the major NCD-related deaths include cardiovascular diseases account for 17 million deaths, cancers account for 7.6 million deaths, respiratory diseases account for 4.2 million deaths, and diabetes accounts for 1.3 million deaths ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kyomuhendo and Adeola (2021) noted that rising incomes and urbanisation are leading to nutrition transition, with traditional foods being substituted with foods high in meat, fats, refined sugars, and oils. Consequently, there is emergence of communicable and non‐communicable diseases.…”
Section: Emerging Framework For Sustainable Agriculture and Food Sysmentioning
confidence: 99%
“…Some of these changes are as a result of technological advancements in form of mechanization, increased awareness of chemicals and chemical use, favourable and non‐favourable government policies (Abubakar & Attanda, 2013). Some challenges and problems associated with non‐use of cleaner agricultural production (Verma, Jaiswal, Meena, Kumar, & Meena, 2015) could lead to nutritional and health challenges (Kyomuhendo & Adeola, 2021). Not practising sustainable agriculture could further reduce soil fertility and natural resources found in the soil.…”
mentioning
confidence: 99%
“…Perceiving that foods are healthy is a key determinant in their consumption [ 4 , 5 , 6 ]. Proof of this can be seen, for example, in the worldwide growth of the organic food market [ 7 ], as it is generally perceived to be a healthier food choice [ 8 , 9 ], or adherence to a Mediterranean diet for its beneficial health effects [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%